Karakterisasi, Desulfurisasi Dan Deashing Batubara Asal Sulawesi Secara Flotasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2005)
ABSTRAK The coal rich with carbon content can be used as fuel alternative for substitution of fuel oil and gas. The coal reserve in Indonesia is large but its quality is relatively low. Coal from Sulawesi until right now can not be optimally used because the sulphur and ash content are relatively high. Desulfurization and deashing of Mallawa coal (from Sulawesi) done in a column flotation using the surfaktan of Crude Palnz Oil ( CPO). Searching optimum condition gives maximum result of desulphurization of coal. The content of sulphur was analyzed with the UV-spectrOphotometer, and the calorivilic value, was measured with the bomb calorimeter. Three optimum conditions of flotation are time of flotation of 40 minutes, dimension of column flotation LID =21 and pH of mixture slurry 6.5, in which the removal of sulphur is 60% and the removal of ash is 22%. The Mallawa coal belongs to the clases of sub-bituminous with the characteristics of before and after flotation are: total sulphur 3.28 and 1.33%, ash 12.23 and 9.03%, fixed carbon 45.41 and 47.98% and calorivilic value 5825 and 5975 kcal/kg. Coal treated at the three optimum conditions still can not meet the standards for fuel in industry, so further process optimization is need. Keywords: ash, coal, flotation, sulphur